Low T3 syndrome is associated with the severity of myelin oligodendrocyte glycoprotein antibody-associated disease exacerbation - Wu, Yuqing; Zhou, Hao; Ci, Xiaojiao; Lu, Jie (Frontiers in Neuroscience, 2024)
Background: Myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD) is a rare autoimmune inflammatory disease of the central nervous system, (CNS) different from multiple sclerosis (MS) and neuromyelitis optica spectrum disorder (NMOSD). While numerous studies have delved into the involvement of thyroid antibodies (ATAbs) and thyroid function in NMOSD and MS. The objective of this study is to explore the clinical significance of thyroid dysfunction and ATAbs abnormalities in adult patients with MOGAD. Methods: 36 adult inpatients diagnosed with MOGAD and 47 sex-and age-matched healthy controls were enrolled. Patients were divided into two groups based on the presence or absence of low T3 syndrome. Demographics, clinical characteristics, and results of auxiliary examinations were compared across the subgroups. Moreover, an analysis was conducted to explore the correlations between thyroid hormone levels and Expanded Disability Status Scale (EDSS) scores.Results: Thyroid dysfunction was notably more frequent in MOGAD patients than healthy controls (p＜0.0001), particularly low T3 syndrome (p=0.03). Furthermore, subgroup analyses revealed that the low T3 syndrome group exhibited higher EDSS scores and a higher proportion of individuals with EDSS scores > 3, in comparison to the non-low T3 syndrome group. (p=0.014, p=0.046). However, no significant differences were observed in demographic characteristics, annual relapse rates, clinical phenotypes, laboratory and MRI results, and EEG abnormalities between the two groups. Additional Spearman's analysis showed significantly negative correlations between the TT3 and FT3 levels with EDSS scores (r = -0.367, p = 0.028; r = -0.377, p = 0.024). Typical brain lesions and paralateral ventricle lesions were significantly rare in patients with positive ATAbs compared to those with negative ATAbs (p=0.0001, p=0.03), although the incidence of ATAbs abnormalities did not differ significantly between MOGAD patients and healthy controls.Conclusions: Overall, this study confirmed thyroid dysfunction, especially low T3 syndrome, is frequent in adult MOGAD patients. Patients with low T3 syndrome exhibited elevated EDSS scores and a significantly higher incidence of unfavorable condition. additionally, the correlation analysis model manifests that FT3 and TT3 levels were negatively correlated with EDSS scores. These evidences indicate that low T3 syndrome is associated with the severity of MOGAD exacerbation.